2017
DOI: 10.1007/s00251-017-0999-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin M gene association with autoantibody reactivity and type 1 diabetes

Abstract: Several lines of evidence show that autoimmune responses evolving in type 1 diabetes (T1D) patients include the generation of multi-reactive autoantibody (AutoAb) repertoires, but their role in T1D pathogenesis remains elusive. We tested the hypothesis that variants at the immunoglobulin heavy chain (IGH) locus are genetic determinants of AutoAbs against pancreatic antigens and contribute to T1D susceptibility. With this aim, two independent study designs were used: a case-control study and a family-based coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…2; Table S2). This region, included within the immunoglobulin heavy chain (IGH) cluster (Lefranc et al 2009;Massari et al 2009;Matiasovic et al 2009;Bao et al 2010;Mineccia et al 2012;Hwang et al 2018;Martin et al 2018), harbours the immunoglobulin heavy constant mu (IGHM) gene, previously associated with autoantibody reactivity and T1D (Rolim et al 2017), and 36 novel ENSEMBL genes, predicted based on cDNA sequence information from dog, with 29 of them containing immunoglobulin-like domains (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2; Table S2). This region, included within the immunoglobulin heavy chain (IGH) cluster (Lefranc et al 2009;Massari et al 2009;Matiasovic et al 2009;Bao et al 2010;Mineccia et al 2012;Hwang et al 2018;Martin et al 2018), harbours the immunoglobulin heavy constant mu (IGHM) gene, previously associated with autoantibody reactivity and T1D (Rolim et al 2017), and 36 novel ENSEMBL genes, predicted based on cDNA sequence information from dog, with 29 of them containing immunoglobulin-like domains (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Rolim et al (2017) performed a human casecontrol study and a family-based cohort comprising a total of 240 T1D patients, 172 first-degree relatives and 130 unrelated healthy controls, and they proved that variants at the IGH cluster are genetic determinants of autoantibodies against pancreatic antigens and contribute to T1D susceptibility. Our results are in line with these findings and further support the idea that control of autoantibody generation by polymorphisms in the IGH cluster may be a component of the genetic susceptibility to DM not only in humans, but also in dogs.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, reduced total plasma IgM has recently been reported in school aged children with type 1 diabetes 28 . Certain variants of the IGHM gene locus have been associated with an increased risk to type 1 diabetes 29 , 30 . Interestingly, in a plasma proteomic study of twins, both IGHM and its binding partner CD5L were reported among the top proteins, that were mostly affected by heritability 20 .…”
Section: Discussionmentioning
confidence: 99%
“…IgM antibodies are involved in the recognition and elimination of precancerous and cancerous lesions, have been found to be upregulated in breast cancer [ 58 ] and were considered a biomarker for recurrence [ 59 ]. IGHM also retained a significant prognostic impact on the density of intratumoural CD20+ B cells [ 60 ] and was associated with type 1 diabetes [ 61 ]. IGHM is involved in oxidative stress and in skin regeneration [ 62 ], suggesting that it may be involved in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%